Wiersz jesienny jako przedmiot badań: propozycja genologiczna - Mikołajczak, Małgorzata (Zagadnienia Rodzajów Literackich, 2019)
The article is concerned with the status and features of the autumn poem as a poetic form well-known to both authors and readers. This poem does not fit the traditional genological taxonomy and it can be characterized from both the perspective of thematic criticism and from poetics based on the prototype concept of the genre. The author focuses on this second way and suggests that the autumn poem should be considered as a polytypic concept. It includes a set of types separated according to criteria that refer to different planes of text. She proves that such an approach may be useful in studying both the communications situation and phenomena of popularity of the phenomenon.